2021
DOI: 10.1111/myc.13378
|View full text |Cite
|
Sign up to set email alerts
|

Novel cases of cutaneous phaeohyphomycosis by Alternaria alstromeriae, Epicoccum tritici and Phialemonium obovatum from North India

Abstract: Background A growing number of non‐dermatophytic moulds and yeasts with the ability to act as human pathogens are reported every year. Dematiaceous fungi cause phaeohyphomycosis which encompasses a broad spectrum of diseases ranging from superficial (cutaneous and subcutaneous) to disseminated infections. Such fungal infections are responsible for causing significant morbidity and mortality, frequently in immunocompromised patients and rarely in immunocompetent patients. Objectives To investigate the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 66 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…In India, cases of Alternaria alstromeriae, Epicoccum tritici, and Phialemonium obovatum have been reported [13].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…In India, cases of Alternaria alstromeriae, Epicoccum tritici, and Phialemonium obovatum have been reported [13].…”
Section: Epidemiologymentioning
confidence: 99%
“…C. cassiicola has only been reported in less than 10 cases [10]. Sharma et al identified two new agents isolated for the first time in the world (A. alstromeriae, E. tritici) and another one isolated for the first time in India (P. obovatum) [13]. P. verrucosa can be isolated from soil, wood, and vegetation and has been reported in cases of subcutaneous phaeohyphomycosis [27].…”
Section: Causative Agentsmentioning
confidence: 99%
See 3 more Smart Citations